Dipole charge density mapping integrated in remote magnetic navigation: First-in-human feasibility study - Rita B. Gagyi; Anna M.E. Noten; Sip Wijchers; Sing-Chien Yap; Rohit E. Bhagwandien; Mark G. Hoogendijk; Tamas Szili-Torok (International Journal of Cardiology: Heart & Vasculature, 2022)
Aims: Robotic magnetic navigation (RMN) provides increased catheter precision and stability. Formerly, only the CARTO 3 mapping system was integrated with the RMN system (CARTO-RMN). Recently, a novel high-resolution non-contact mapping system (AcQMap) has been integrated with the RMN system (AcQMap-RMN) for the treatment of atrial fibrillation (AF) and atrial tachycardias (AT). We aim to compare the safety, efficiency, and efficacy of AcQMap-RMN with CARTO-RMN guided catheter ablation (CA) procedures. Material and methods: In this prospective registry, procedural safety efficiency and outcome data from total of 238 consecutive patients (147 AcQMap-RMN and 91 CARTO-RMN patients) were compared. Results: AcQMap-RMN is non-inferior in the primary endpoint of safety as compared to CARTO-RMN across the whole group (overall procedural complications in 5 (3.4%) vs. 3 (3.3%) patients, p = 1.0). Overall procedure durations were longer and associated with more fluoroscopy use with AcQMap-RMN (172.5 vs. 129.6 min, p < 0.01; 181.0 vs. 131.0 mGy, p = 0.02, respectively). Procedure duration and fluoroscopy use decreased significantly between the first 30 and the last 30 AcQMap-RMN procedures. The AcQMap-RMN system had fewer recurrences after persistent AF ablations and was non-inferior in paroxysmal AF patients compared to CARTO-RMN at 12 months (36.6% vs. 75.0%, p = 0.04, PAF 6.6% vs. 12.5%, p = 0.58; respectively). CA of AT outcomes were better using the AcQMap-RMN system (1 year recurrence 17.1% vs. 38.7%, p < 0.05). Conclusion: AcQMap-RMN integration has no negative impact on the excellent safety profile of RMN guided ablations. It improves outcomes of CA procedures for persAF and AT but requires longer procedure times and higher fluoroscopy use during the initial learning phase.